Cryopreservation and characterization of canine preantral follicles - Rôlo, José Luiz Jivago de Paula (2018)
The aim of this study was to define the population, morphological and ultrastructural characteristics of bitch preantral follicles (PAFs) and to compare the effects on the morphology of PAF of two cryopreservation techniques - slow freezing (SF) and vitrification (V) - of bitches' ovarian tissue. The average population (number per ovary) of PAFs was 48,541 ± 18,366, where 94.25% were primordial (45,145 ± 16,076). The average diameter of the primordial follicles was 27.5 ± 4.2 μm. The overall percentage of morphologically normal PAFs was 93.66 ± 6.81% for the control group, 86.16 ± 11.05% after SF and 68.14 ± 12.75% after V. The percentage of normal primordial follicles was 96.69 ± 4.72% in control, 89.51 ± 10.39% in SF and 75.32 ± 9.23% in V. There was no significant difference in the overall percentage of normal PAFs among SF and the control. However, slow frozen follicles presented ultrastructural damage, while vitrified primordial and primary follicles were well preserved. In conclusion, although slow freezing seemed to be a good preserving method, vitrification was more effective than slow freezing in preserving the ultrastructure of primordial and primary follicles of bitches.